(untitled) (Journal of Pharmaceutical Negative Results, 2020)
Objective: To systematically examine the prognostic significance of isocitrate dehydrogenase 1 (IDH1) mutations according to country region.Methods: We searched five electronic databases from inception to September 2019 for relevant studies. A meta‑analysis was performedafter evaluating which studies met the inclusion criteria. Thirty‑seven were identified for this meta‑analysis, comprising 5141 GBM patients.Results: The benefit of overall survival (OS) was the hazard ratio (HR), 0.67 (95% confidence interval [CI], 0.61–0.74). When subgroup analysisby country region, the pooled HR for the Eastern population studies was 1.15 (95% CI: 0.97–1.35) with no association between IDH1 mutationand OS of GBM, while IDH1 mutation still had a significant survival advantage in the Western population studies(HR: 0.51, 95% CI: 0.45–0.57).Conclusions: This study confirmed that IDH1 mutation is an independent prognostic factor for patients with GBM. However, a topographicrelationship was observed in the results, and an association between this genetic mutation and prognosis should be explored in future studies.